2013
DOI: 10.1007/978-3-319-01300-8_4
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Decompositions and Coalescing Eigenvalues for Matrices Depending on Parameters

Abstract: In this work, we consider symmetric positive definite pencils depending on two parameters. That is, we are concerned with the generalized eigenvalue problem A(x) − λB(x), where A and B are symmetric matrix valued functions in R n×n , smoothly depending on parameters x ∈ Ω ⊂ R 2 ; further, B is also positive definite. In general, the eigenvalues of this multiparameter problem will not be smooth, the lack of smoothness resulting from eigenvalues being equal at some parameter values (conical intersections). We fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…By construction, these functions are holomorphic in the vicinity of ν * where eigenvalues coalesce, as this was already mentioned in [27,18,16,23] and in [4, p. 66]. The regularity of these two functions can easily be checked by injecting the local behavior given in Eq.…”
Section: Analytic Auxiliary Functionmentioning
confidence: 82%
“…By construction, these functions are holomorphic in the vicinity of ν * where eigenvalues coalesce, as this was already mentioned in [27,18,16,23] and in [4, p. 66]. The regularity of these two functions can easily be checked by injecting the local behavior given in Eq.…”
Section: Analytic Auxiliary Functionmentioning
confidence: 82%
“…For hermitian problems, it can be shown that the veering phenomenon is a consequence of the eigenvalue problem degeneracy for a complex value of the parameter [31,38,42]. Indeed, if the parameter of the problem is extended in the complex-plane, the K (and M) matrices becomes non-Hermitian and eigenvalues and eigenvectors could coalesce.…”
Section: Radius Of Convergence and Exceptional Point Locationmentioning
confidence: 99%
“…As a consequence, for a given path in the complex parametric space, one can continuously change from one branch to the other. For instance, when ν move along the real axis, it explains the eigenvector switching at veering point [31]. Puiseux series are the only representation that allow capture the Riemann surface topology and to follow each modal branch.…”
Section: Puiseux Seriesmentioning
confidence: 99%
See 2 more Smart Citations